Juridical Review of Duties and Functions of Bhabinkamtibmas In Maintaining Security and Order in Sempu Village, Blora Regency - Suwoko Suwoko; Edi Pranoto (CV. Publikasi Indonesia, 2023)
Indonesia is a constitutional state with laws governing all aspects of social life, including the Indonesian National Police (Polri), which is responsible for maintaining public order and security, law enforcement, protection, and service to the community. To enhance community policing, Polri adopted the concept of